Comparación de los objectivos vitales de los psicólogos LatinoAmericanos y Estadounidenses - Stephenson, Matilde Kejner; Nath, Raghu (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
An inventory of vital objectives was anonymously administered to 41 Latin American psychologists and 62 psychologists from the U. S. A. The subjects were to order the twelve concepts defined in accordance with the importance which they attached to them. The results indicate that the Latin American psychologists and the psychologists from the U. S. A. perceive in a more or less similar way the importance of the twelve objectives presented in spite of the fact that there are certain differences with reference to leadership, family, wealth and social prestige.